Analisis Pengelolaan Keuangan Startup Dalam Mencapai Keberlanjutan Bisnis - Jua Anugrah Jaya Laoli (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study examines the strategic dilemma faced by startups in choosing between aggressive market share growth and achieving short-term profitability. In the digital economy era of 2026, a shift in investor sentiment from "growth at all costs" to "profitable sustainability" forces management to rebalance. Using a descriptive qualitative approach, this study finds that expansion strategies without considering positive unit economics trigger fatal liquidity risks. The results indicate that the optimal trade-off point is reached when customer acquisition costs (CAC) can be covered by customer lifetime value (LTV) within a measurable cycle, so that expansion still supports future profitability.